A prospective study of cases of intestinal obstruction and role of conservative expectant management - Pandey, Yuktansh (International Surgery Journal, 2018)
Background: Intestinal obstruction continues to be a common surgical emergency throughout the world and its management protocol has evolved over years. In our study we aimed to provide a complete epidemiological description of intestinal obstruction in adult age group patients in a tertiary care hospital in Northern India. Methods: This is a prospective study of patients belonging to age group more than 12 years admitted in our unit with clinical features suggestive of intestinal obstruction from September 2011 to December 2013 at R. N. T. Medical College, Udaipur. The study comprised of 134 patients. Results: Intestinal obstruction contributed to 6.5% of all surgical admissions. It was nearly twice more common in males. 43% patients presented with features of acute intestinal obstruction in comparison to 57% who presented with features of sub-acute intestinal obstruction. Most common cause observed was obstruction due to intra-abdominal adhesions followed by abdominal tuberculosis 48 and 29 percent respectively. Features of intestinal obstruction resolved in 60% patients with conservative management. Adhesions, abdominal tuberculosis and malignancy counted for majority of patients with sub-acute obstruction. Emergency surgery was done in 32% of patients and 36.5 % of patients were discharged non-operatively. Planned Surgery after successful expectant management was done in 24 % patients. Most frequently seen complication was wound site collection (72.5%) followed by respiratory tract infections (49%). Total mortality in our study was 12.6% of which 41% was post-operative mortality and 59% mortality seen in patients who expired during conservative management. Conclusions: This study demonstrates that intra-abdominal adhesions and abdominal tuberculosis account for most cases of intestinal obstruction in countries like India. A watchful expectant management can be tried in patients with prior operative history and those with history of tuberculosis.